"Just Make Sure you Can Get up and Parent the Next Day": Understanding the Contexts, Risks, and Rewards of Alcohol Consumption for Parents. Issue 3 (July 2015) - Wolf, Jennifer Price; Chávez, Raúl
Little is known about how parents make drinking decisions and weigh the risks and rewards of alcohol consumption in specific contexts. This qualitative study examined two questions: (a) What factors influence parental drinking decisions in different drinking contexts? and (b) What do parents perceive as the risks and rewards of alcohol consumption in different drinking contexts? Purposive sampling was used to select 60 parents of children aged 10 or younger living in 4 midsized California cities. Data were collected via in-depth, semistructured interviews. Many parents viewed drinking at family get-togethers or parties as protective of children, since the presence of multiple adults and children provide buffers when parents become intoxicated. In contrast, parents noted that drinking at home, and particularly drinking alone, transmitted potentially negative messages. Social pressures and contexts influence alcohol consumption among parents and could provide potential avenues for intervention against alcohol-related harm.